Genome-wide identification of zero nucleotide recursive splicing in Drosophila - Duff, Michael O.; Olson, Sara; Wei, Xintao; Garrett, Sandra C.; Osman, Ahmad; Bolisetty, Mohan; Plocik, Alex; Celniker, Susan E.; Graveley, Brenton R. (Nature (London), 2015)
In flies, some introns contain internal splice sites that cause ‘recursive splicing’, a multi-step removal of a single intron; this study demonstrates that the scope of this regulatory mechanism is much more extensive in flies than had been appreciated, and provides details about the recursive splicing process. Recursive splicing in insects and vertebrates The mechanisms by which the very longest genes in eukaryotic genomes are accurately processed are poorly understood. It was thought that intron removal generally involved a single excisive step. Later studies showed that, in flies, some introns contain internal splice sites that cause 'recursive splicing', in which single introns are removed 'bit-by-bit' in several sequential splicing reactions. Brenton Graveley and coworkers demonstrate that the scope of this regulatory mechanism is much more extensive in flies than had been appreciated. They identify nearly 200 zero-nucleotide exons in Drosophila that are the products of recursive splicing. Jernej Ule and colleagues identify recursive splicing sites in vertebrates, particularly within long genes encoding proteins that are involved in neuronal development. Analysis of the mechanism of their splicing reveals that such splicing sites can be used to dictate different mRNA isoforms. Recursive splicing is a process in which large introns are removed in multiple steps by re-splicing at ratchet points—5′ splice sites recreated after splicing 1 . Recursive splicing was first identified in the Drosophila Ultrabithorax ( Ubx ) gene 1 and only three additional Drosophila genes have since been experimentally shown to undergo recursive splicing 2 , 3 . Here we identify 197 zero nucleotide exon ratchet points in 130 introns of 115 Drosophila genes from total RNA sequencing data generated from developmental time points, dissected tissues and cultured cells. The sequential nature of recursive splicing was confirmed by identification of lariat introns generated by splicing to and from the ratchet points. We also show that recursive splicing is a constitutive process, that depletion of U2AF inhibits recursive splicing, and that the sequence and function of ratchet points are evolutionarily conserved in Drosophila . Finally, we identify four recursively spliced human genes, one of which is also recursively spliced in Drosophila . Together, these results indicate that recursive splicing is commonly used in Drosophila , occurs in humans, and provides insight into the mechanisms by which some large introns are removed.